Exploring the Capacity of the Egyptian Feminist Movement to Shape Policy Responses to Sexual Violence in Egypt - Raway, Gehad (AUC Knowledge Fountain, 2024)
This study aims to contribute to the literature on feminist movements and its impact on public policies, providing insights and recommendations to strengthen the Egyptian feminist movement's capacity to combat sexual violence effectively. The study explores the capacities of the Egyptian feminist movement to shape policy responses to sexual violence over a timeline extending from 2005 to 2021, within the context of the significant social and political transformations that preceded and followed the January 2011 revolution. The Egyptian feminist movement evolved through its history with times of growth and decline, characterized by continuity and resilience. The literature and findings indicate that sexual violence was a central issue on the Egyptian feminist movement agenda in 2011, where many struggles and various strategies were utilized to combat it and achieve policy responses that ensure the state's obligations to protect women. However, the way still quite long to eliminate sexual violence in Egypt. Using a qualitative methodology and relying on 17 semi-structured interviews with feminist activists in various positions, parliamentarians, and feminist experts with diverse experiences inside and outside the movement, this study explores the strategies adopted by the movement, the challenges it faced, the external and internal factors affecting its effectiveness, and to what extent these factors have influenced its capacities to shape policy responses to sexual violence, in addition to identifying strengths and opportunities that can be leveraged. The main findings reveal that the feminist movement has achieved significant gains, including legal reforms, state acknowledgment of sexual violence, and raising public awareness regarding sexual violence. However, the movement is still constrained by the political context, limited resources, and internal organizational challenges. The study emphasizes the need for continuous efforts, enhanced internal dialogue and coordination within the movement, and the review and development of the existing strategies while simultaneously investing in strategic alliances and leveraging digital platforms to enhance the movement's impact.